Fungsionalisasi Kartu Tani terhadap Pemenuhan Kebutuhan Pupuk Bersubsidi kepada Petani di Kabupaten Cianjur Perspektif Undang-Undang Nomor 19 Tahun 2013 tentang Perlindungan dan Pemberdayaan Petani - Saptaning Ruju Paminto; Ibrahim Khalil Ahmad; Zenal Syaepul Rohman; Ahdi Hidayat; Tegar Wahyu Hidayat; Fakhrian Yudiansyah (Hukum Inovatif : Jurnal Ilmu Hukum Sosial dan Humaniora, 2024)
Law No. 19 of 2013 on the Protection and Empowerment of Farmers aims to improve farmers' welfare through various programs, including fertilizer subsidies. However, the distribution of subsidized fertilizers often faces issues such as misallocation, delays, and misuse. The Farmer Card (Kartu Tani), an innovation to facilitate the distribution of subsidized fertilizers, has significant potential to address these problems. This study aims to evaluate the effectiveness of the Farmer Card in the distribution of subsidized fertilizers, identify the challenges faced by farmers in its use, and propose solutions for the optimization of the Farmer Card. Using a descriptive qualitative approach through literature review, this study finds that the main challenges include technical issues, lack of socialization, bureaucratic hurdles, and farmers' distrust of new technology. Proposed solutions include enhancing technological infrastructure, providing intensive training for farmers, and simplifying administrative procedures. The study's results indicate that improvements in these aspects can enhance the effectiveness and transparency of subsidized fertilizer distribution through the Farmer Card.